Influence of Body Mass Index, Handedness and Gender on Ruler Drop Method Reaction Time among Adults - Jha, Reena Kumari; Thapa, Samjhana; Kasti, Roshan; Nepal, Ojashwi (Journal of Nepal Health Research Council, 2020)
Background: The interval between stimulus and response is called reaction time. It measures the sensorimotor function and performance of an individual. It involves stimulus processing, decision making and response programming. Many factors such as age, gender, handedness, physical fitness, sleep, fatigue, distraction, personality type and type of stimulus have been shown to affect reaction time. Thus the aim of this study was to assess the effect of body mass index, handedness and gender on reaction time. Methods: A cross-sectional study was conducted in the Department of Physiology, Kathmandu University School of Medical Sciences, from October 2019 to December 2019, among 113 student volunteers. Height and weight were recorded and body mass index was then calculated. In ruler drop method, the students were made to sit with their forearm resting on a flat horizontal table surface, with their open hand at the edge of the surface. When the examiner suspended and released the ruler vertically the students were instructed to catch it as quickly as possible. Results: Females had a faster reaction time than males when testing either hand (178.46±17.56 Vs 195.99±15.67; right hand) and (184.25±17.02 Vs 199.57±15.91; left hand). In females, right hand responded faster than left hand. In both gender, reaction time was faster in normal weight compared to overweight individuals but it was statistically insignificant. Conclusions: Females responded faster than males. Right hand had shorter reaction time than left hand in females. Reaction time was insignificantly prolonged in overweight individuals. Keywords: Body mass index; reaction time; ruler drop method